2020
DOI: 10.1111/jfb.14311
|View full text |Cite
|
Sign up to set email alerts
|

Measuring maximum oxygen uptake with an incremental swimming test and by chasing rainbow trout to exhaustion inside a respirometry chamber yields the same results

Abstract: This study hypothesized that oxygen uptake (ṀO 2) measured with a novel protocol of chasing rainbow trout Oncorhynchus mykiss to exhaustion inside a static respirometer while simultaneously monitoring ṀO 2 (ṀO 2chase) would generate the same and repeatable peak value as when peak active ṀO 2 (ṀO 2active) is measured in a critical swimming speed protocol. To reliably determine peak ṀO 2chase , and compare to the peak during recovery of ṀO 2 after a conventional chase protocol outside the respirometer (ṀO 2rec),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 56 publications
(100 reference statements)
0
33
0
Order By: Relevance
“…in seconds, after the cessation of exercise) was also often not provided (criterion 44). This is important because data processing procedures can bias estimates of MMR (Zhang et al, 2020), including the duration of the slope used to estimate MMR and the specific method of determining the maximum rate of oxygen uptake during recovery after exercise (criterion 49). Our survey revealed that both criteria were relatively underreported but, given emerging awareness of their importance, it is vital that authors provide these details going forward.…”
Section: Survey Of the Existing Literaturementioning
confidence: 99%
“…in seconds, after the cessation of exercise) was also often not provided (criterion 44). This is important because data processing procedures can bias estimates of MMR (Zhang et al, 2020), including the duration of the slope used to estimate MMR and the specific method of determining the maximum rate of oxygen uptake during recovery after exercise (criterion 49). Our survey revealed that both criteria were relatively underreported but, given emerging awareness of their importance, it is vital that authors provide these details going forward.…”
Section: Survey Of the Existing Literaturementioning
confidence: 99%
“…Individuals were fed to satiation every 3-5 days using human-grade market squid (Doryteuthis opalescens) and mackerel (Scomber japonicus) and were fasted for a minimum of 48 hr before experiments to remove the influence of specific dynamic action on metabolic rate estimates. Experimental conditions for Rainbow Trout and Atlantic Salmon can be found in Zhang et al (2016Zhang et al ( , 2020, respectively.…”
Section: A Ppe N D I X 1 a N I M A L Acqu I S Iti O Nmentioning
confidence: 99%
“…All experiments were carried out using a chase-to-exhaustion protocol where each individual was manually chased by hand in a tank large enough to allow unimpeded burst-swimming Zhang et al, 2016Zhang et al, , 2020. The focal individual was deemed exhausted once it stopped bursting away and began resting on the bottom of the chase tank between stimuli (usually after 4-7 min of chasing).…”
Section: Co Llec Ti O N O F Ox Yg E N Co N S U M P Ti O N Datamentioning
confidence: 99%
“…Of greater concern is that chasing a fish outside of a respirometer potentially underestimatesṀO 2max [88] and so this problem has been avoided by adding a simple chasing device to a standard respirometry chamber (Figure 3d). This way a fish can be agitated to generate a reliableṀO 2peak [88] and even repeatedly agitated without having to remove the fish from the respirometer. while it is continuously agitated for 15 min inside a respirometer (ṀO 2chase ) at normoxia (>80% air sat.).…”
Section: Individualizing the Limiting-oxygen Concentration (Loc) Performance Curvementioning
confidence: 99%
“…Maintaining the chasing apparatus at the same DO as the respirometer would be another challenge. Of greater concern is that chasing a fish outside of a respirometer potentially underestimates Ṁ O 2max [ 88 ] and so this problem has been avoided by adding a simple chasing device to a standard respirometry chamber ( Figure 3 d). This way a fish can be agitated to generate a reliable Ṁ O 2peak [ 88 ] and even repeatedly agitated without having to remove the fish from the respirometer.…”
Section: Individualizing the Limiting-oxygen Concentration (Loc) Performance Curvementioning
confidence: 99%